Gonadotrofina coriônica equina (ECG) na superestimulação ovariana prévia a opu em vacas braford: efeito sobre o crescimento folicular e na cinética de fecundação e desenvolvimento embrionário in vitro - Ribas, Bibiana Noal (2017)
Due to the great need to increase the genetic material in cattle, the OPU / PIV techniques have been applied in a large scale in order to obtain a larger number of products born per year of selected females. However, some animals have a low number of follicles available for OPU, while others have a low rate of oocyte conversion in embryos. In this context, works that seek to maximize OPU / PIV results are essential. One of the alternatives is to pharmacologically manipulate follicular development to obtain more competent oocytes for in vitro fertilization and embryonic development. Therefore, the objective of this study was to evaluate the effect of different doses of equine Chorionic Gonadotrophin (eCG) on a protocol prior to OPU, on the follicular development, number and quality of oocytes recovered as well as potential for fertilization and in vitro embryo development. Sixteen Braford donor cows were submitted to 4 OPU sessions with a 15 day interval between each aspiration (n = 16 per treatment, cross over), to evaluate the effect of the eCG dose the donors were divided according to the respective treatments (Control = zero, eCG200 = 200UI of eCG, eCG400 = 400UI of eCG, and eCG800 = 800UI of eCG). At the beginning of the synchronization protocol (D0), the donors received 2 mg of estradiol IM benzoate, 12.5 mg of dinoprost tromethamine IM and a slow intravaginal P4 release device. On day 3, the donors were given a dose of eCG according to each treatment and on day 6, the P4 device was removed and the donors were subjected to OPU. Before OPU, ovarian follicles were visualized, measured and classified according to the diameter in small (< 6 mm), medium (6-10 mm) and large (> 10 mm). After OPU, viable ix oocytes from each cow were taken to IVM and IVF in groups according to treatments. IVM was performed for 24 hours at 39°C in modified TCM 199. For in vitro fertilization, the sperm of a Bos taurus bull of proven fertility were selected by Percoll gradients and co-incubated with the oocytes for 18 h. After IVF, 50% of probable zygotes were evaluated for fertilization rate by epifluorescence. The remaining oocytes were transferred to drops of SOFaaci and cultured in vitro for evaluation of the cleavage rate, time of the first cleavage and cell number at 48 hours in an embryonic monitoring system. Statistical analyzes were performed using ANOVA and the means were compared by the Tukey test (P < 0.05). There was no difference in the number of follicles, quantity and morphological quality of the oocytes obtained between the treatments (P < 0.05). The oocyte recovery rate was similar between the eCG treated groups, but lower than the Control (p < 0.001). However, the eCG800 had a greater number of medium and large follicles (> 6 mm and > 10 mm, P <0.00001). In addition, the eCG800 had a higher normal fertilization rate (54.3 ± 8.5) and a lower rate of polyspermy (5.7 ± 4.0) than the other groups (P < 0.05). The eCG800 and Control had a higher cleavage rate than the other treatments (68.6 ± 7.9 and 75.6 ± 6.8), respectively. There was no difference at the time of the first cleavage and in the average number of cells at 48 h between treatments. Based on these data, it can be concluded that the dose of 800UI of eCG increased the proportion of follicles > 6mm, providing the highest rate of normal fertilization and a reduction in the rate of polyspermia in relation to Control and the other doses of eCG, without impairing the kinetics of embryonic development until at 48 hours.